Protection, Participation, and Public Awareness : Indonesia Coral Reef Rehabilitation and Management Project - Kuehnast, Kathleen (World Bank, Washington, DC, 2012)
The Indonesia Coral Reef Rehabilitation and Management Project (COREMAP) is the first operation supported by the World Bank to focus exclusively on coral reef ecosystems. COREMAP is being implemented in 10 provinces over 15 years, during which period the communities are given incentives, training, and resources to protect the coral reefs. Social Development best practice elements identified in this project were: 1) Participatory processes in preparation and implementation; 2) Institutionalized mechanisms for decentralized implementation; and 3) Ongoing monitoring and evaluation of social development outcomes by the government and community. Specific lessons learned were: Participation of local communities in project design builds sustainability and leads to greater ownership. Creating partnerships between local universities and NGOs supports project implementation. Capacity building on the local level enable communities to participate in ecosystem management. Establishing conflict resolution mechanisms facilitates access of different user groups to natural resources.